Latin America : a hub for agrobiotechnological innovations - Segretin, Maria Eugenia; Soto, Gabriela Cynthia; Lorenzo, Christian Damian (Oxford University Press, 2025)
Background: Modern biotechnology is one of the last century’s major advances in human science. Particularly in the agronomical field, the landscape of crop improvement technologies has witnessed a great expansion, driven by the integration of molecular and genetic engineering methodologies into the breeding toolbox. Latin America (LATAM) serves as a pioneering region in incorporating such techniques with several countries swiftly embracing these technologies. Scope: This review aims to give a comprehensive overview of the elements that influenced agrobiotech acceptance in LATAM countries and how such cases could provide support for upcoming technologies to be considered worldwide. Conclusions: Nearly 50 years of biotech breakthroughs have provided humankind with an impressive portfolio of tools already integrated into several life-science areas. The agronomical field has greatly progressed thanks to technologies derived from genetically modified organisms and great promises are being made to also incorporate genome-editing products. LATAM provides a prime example of how early introduction of novelties in the crop production chain can result in improved yields, paving the way for future developments to be easily integrated into the technological ecosystem of a region. The example set by LATAM can also be useful for the present gene-editing regulatory scenario. With several countries presently on the path to approving these methods in their current crop systems, basing their next steps on the example of LATAM could represent a safe and practical pathway towards a new agronomical revolution.